On the local mode behaviour of the XH2/XD2 and XD/XH fragments with respect to the deuterated species of the near local mode XH3(C3v ) molecule - Ulenekov (Ulenikov) O. N. Oleg Nikolaevich (2009, 2009)
Title screen